2015
DOI: 10.1111/iej.12517
|View full text |Cite
|
Sign up to set email alerts
|

Combined and independent cytotoxicity of sodium hypochlorite, ethylenediaminetetraacetic acid and chlorhexidine

Abstract: CHX was significantly more cytotoxic than NaOCl and EDTA. NaOCl was significantly more cytotoxic than EDTA. The combined action of irrigants did not produce a significant increase in their cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 55 publications
2
30
1
1
Order By: Relevance
“…However, with EDTA diluted to 0.5%, the results were conflicting (16). In addition, our result was contrary to that of other investigators who concluded that the cytotoxic effect of 15% and 17% EDTA is time-and dose-dependent (3,5,14,15,17,25). These conflicting results may be explained by the use of a variety of methods other than the MTT assay used in the present study to evaluate the cytotoxic potential of chelating agents (25).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…However, with EDTA diluted to 0.5%, the results were conflicting (16). In addition, our result was contrary to that of other investigators who concluded that the cytotoxic effect of 15% and 17% EDTA is time-and dose-dependent (3,5,14,15,17,25). These conflicting results may be explained by the use of a variety of methods other than the MTT assay used in the present study to evaluate the cytotoxic potential of chelating agents (25).…”
Section: Discussioncontrasting
confidence: 94%
“…The chelating agents were tested at clinically used concentrations: 1% AA, 0.2% CH, and 17% EDTA. Cell viability assay evaluates cytotoxic effects by measuring the behavior of cell cultures against a given substance and may be indicative of effects caused in vivo, although its results cannot be directly extrapolated to the in vivo condition (5). Different time points were used to mimic the effect of the chelating agents immediately after contact with the cells and the effect of residual components over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In this study, except for the control group, increased exposure time with regard to all test solutions increased toxicity. Vouzara et al 26 reported that an increase in the exposure time of EDTA and CHX on human lung fibroblasts cell line (6, 24 hours) increased toxicity. Li et al 27 reported that CHX toxicity on the murine macrophage cell line increased with the increase in exposure time (1, 2, 4 hours).…”
Section: Discussionmentioning
confidence: 99%
“…A single solution cannot entirely fulfil all these actions, hence the need for substance association [5][6][7][8][9]. However, in conjunction with the considerable improvement of cleaning the root canal harmful effects were also noticed.…”
mentioning
confidence: 99%